IDENTIFICATION OF SINGLE NUCLEOTIDE POLYMORPHISMS ON CATTLE BREEDS IN INDONESIA USING BOVINE 50K - Puji Lestari; Habib Rijzaani; Dani Satyawan; Anneke Anggraeni; Dwinita Wikan Utami; Ida Rosdianti; Muchamad Lutfi; I Made Tasma (Indonesian Agency for Agricultural Research and Development, 2015)
Single nucleotide polymorphisms (SNPs) abundant in bovine genome influence genetic variation in biological mechanism. The study aimed to identify SNPs on Indonesian cattle breeds and analyze their genetic diversity using Bovine 50K SNP chip. Twenty eight